Extruded corn, sorghum, wheat, and barley for finishing pigs - B T Richert; Terry L Gugle; Robert H Hines; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1992)
Eighty barrows (113.7 lb average initial weight) were used to determine the effects of extruding corn, sorghum, wheat, and barley on growth performance, carcass merit, nutrient digestibility, and changes in stomach morphology of finishing pigs. Treatments were grain source (com, sorghum, wheat, and barley) and processing procedure (grinding vs extrusion) arranged as a 4 x 2 factorial. Grinding was in a Jacobson hammermill and extrusion was in an Insta-Pro extruder. Pigs fed com had improved average daily gain (ADG), feed/gain (F/G), DM digestibility, and N digestibility compared to the other grain sources. Diets with barley supported the poorest growth performance and nutrient digestibilities, with sorghum and wheat intermediate. Extrusion of the cereal grains did not affect ADG but increased efficiency of gain by 4, 9, 6, and 3% for corn, sorghum, wheat, and barley, respectively. Digestibilities of DM and N were also increased on average by extrusion processing, with barley responding the most (9 and 12% increases for DM and N digestibilities) and wheat responding the least (no improvement). Overall, extrusion processing improved nutritional value of cereal grains for finishing pigs. However, swine producers must be careful to evaluate the overall economic benefits before adopting this or any other new technology.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Process; Extrusion; Sorghum; Wheat; Barley; Corn; Performance; G-F